PENDIDIKAN AGAMA KRISTEN DAN PEMBENTUKAN IDENTITAS GENDER DI KALANGAN REMAJA: PENDEKATAN TEOLOGIS DAN SOSIOKULTURAL - Eliani Salma Sura; Viona Christie Ningsi, Fellix Theodorus Manuakali, Jetry Battu Salombe', Intan Mangase Pongre&# (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
Gender identity is an increasingly complex issue in the modern era, especially amid rapid social changes and the growing discourse on gender. Christian teachings, which emphasize humanity as God's creation, provide an important theological framework for shaping adolescents' views on gender. This study aims to examine the role of Christian religious education in shaping gender identity among adolescents, using a theological and sociocultural approach. Through a literature review method, the research analyzes how Christian religious education conveys theological values about gender and how these teachings interact with the dynamic social and cultural context. The results of the study show that Christian religious education plays a significant role in helping adolescents understand their gender identity, both from a faith perspective and within the social context. Biblical teachings on the roles of men and women provide a strong foundation, yet a sociocultural approach in religious education is needed to bridge the realities of modern adolescent life, which is influenced by media, culture, and ongoing social discussions. The conclusion of this study affirms that the integration of theological and sociocultural approaches in Christian religious education can make a positive contribution to the formation of a healthy gender identity among adolescents, as well as the relevance of Christian teachings in addressing contemporary social challenges